2011
DOI: 10.2304/eerj.2011.10.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing ‘Aspiration’: UK Policy Debates and European Policy Trends

Abstract: Strategies of 'employability' and 'activation' are increasingly favoured in the European Union policy context. These strategies are aimed at fostering inclusion by stressing the responsibility of the individual to participate in education and employment. Similar tendencies can be observed in the United Kingdom (UK) over the last decade, among them a debate on raising young people's aspirations. The article reports first findings from a research project on the construction of 'aspiration' in and through policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 25 publications
0
47
0
3
Order By: Relevance
“…In other contexts, it has been suggested that shifting attention to aspirations-focused policy development for youth would be helpful. In the United Kingdom, for instance, education policy (see Department for Children, Schools, and Families, 2009) has targeted aspirations as an area of concern for young people, and has viewed aspirations-focused policies as crucial to elevating attainment, employability, and social mobility in this population (see Spohrer, 2011). Critics of these educational policies, such as Allen and Hollingworth (2013), have argued that these strategies are "socially and spatially restrictive" (p. 500), and have an asymmetrical impact on young people depending on their social class and geographical locations, among other factors.…”
Section: Study Implicationsmentioning
confidence: 99%
“…In other contexts, it has been suggested that shifting attention to aspirations-focused policy development for youth would be helpful. In the United Kingdom, for instance, education policy (see Department for Children, Schools, and Families, 2009) has targeted aspirations as an area of concern for young people, and has viewed aspirations-focused policies as crucial to elevating attainment, employability, and social mobility in this population (see Spohrer, 2011). Critics of these educational policies, such as Allen and Hollingworth (2013), have argued that these strategies are "socially and spatially restrictive" (p. 500), and have an asymmetrical impact on young people depending on their social class and geographical locations, among other factors.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Youth are frequently presented in policy discourse as suffering from a 'poverty of aspirations' (Spohrer, 2011). In a discursive analysis of governmental speeches, papers and reports, Spohrer (2011) argues that policy discourse positions 'low aspirations' as a cause of social disadvantage, thus presenting the solution to poverty as 'raising aspirations' at the level of the individual. Young people's talk about their own social location and understanding of inequality thus needs to be understood in the context of wider discourses of poverty, meritocracy and aspiration.…”
Section: The Common-sense Of Inequalitymentioning
confidence: 99%
“…professional and social integration, via training programmes'. As the cash welfare state is suspected to foster passivity among its benefi ciaries, which may in turn result in long-term unemployment and social exclusion, strategies of activation are therefore to be seen in the context of changing welfare states (Spohrer 2011 ). As a consequence, while on the one hand, individuals are made more attractive to employers through training and fi nancial incentives, they are also expected to increase their job search activity.…”
Section: The Thinking Behind Active Labour Market Policies Towards Yomentioning
confidence: 99%